2001
DOI: 10.1086/321962
|View full text |Cite
|
Sign up to set email alerts
|

Stream Incision, Tectonics, Uplift, and Evolution of Topography of the Sierra Nevada, California

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
332
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(358 citation statements)
references
References 53 publications
23
332
1
2
Order By: Relevance
“…This area is interesting because it is not very far from the seismically imaged [Verdonck and Zandt, 1994] southern end of the Gorda plate. If the reported tilting of the SN region farther north [Unruh, 1991;Wakabayashi and Sawyer, 2001] has a thermal origin as suggested in section 5.2, then the cessation of subduction of the Gorda plate and associated lateral heat transfer starts farther north than the seismically imaged end of the Gorda plate. The lack of volcanism south of the Lassen volcano (Figure 1) supports this conclusion.…”
Section: Volcanism and Magmatism Along The Sn-br Boundarymentioning
confidence: 93%
See 1 more Smart Citation
“…This area is interesting because it is not very far from the seismically imaged [Verdonck and Zandt, 1994] southern end of the Gorda plate. If the reported tilting of the SN region farther north [Unruh, 1991;Wakabayashi and Sawyer, 2001] has a thermal origin as suggested in section 5.2, then the cessation of subduction of the Gorda plate and associated lateral heat transfer starts farther north than the seismically imaged end of the Gorda plate. The lack of volcanism south of the Lassen volcano (Figure 1) supports this conclusion.…”
Section: Volcanism and Magmatism Along The Sn-br Boundarymentioning
confidence: 93%
“…[49] Geomorphologic studies in SN show that this region has been tilting westward as a single block in the last 10-12 Ma with total uplift of 1.5-2.5 km at the eastern edge; most of the uplift occurring in the last 3 -5 Ma [Unruh, 1991;Wakabayashi and Sawyer, 2001;Stock et al, 2004;Clark et al, 2005]. In addition to its previous elevation as a volcanic arc [Bateman and Wahrhaftig, 1966;House et al, 2001], tilted uplift started approximately with the cessation of subduction and lead to exposure of a huge granitic belt [Bateman and Wahrhaftig, 1966;Hay, 1976;Crough and Thompson, 1977].…”
Section: Tilted Uplift In the Sn And Pb Regionsmentioning
confidence: 99%
“…Negligible additional uplift occurred until after about 5 Ma when the present elevation would have been obtained. This model dates back at least to the time of Waldemar Lindgren (1911) and is based almost entirely on geomorphologic evidence, reinforced lately by potassium-argon ages of overlying late Cenozoic volcanic rocks (Wakabayashi and Sawyer 2001, and comprehensive references therein). Part A of Figure 16 is an attempt to show how this particular uplift history might connect with the western part of the Great Basin Altiplano; the figure involves a gross (more than sixfold) linear extrapolation of the slopes of Eocene Auriferous Gravel calculated and projected by Yeend (1974).…”
Section: Character Of the Western Margin Of The Altiplanomentioning
confidence: 99%
“…5 Ma). For example, Wakabayashi and Sawyer (2001) constructed this scenario from an extensive analysis of current topography coupled with thermochronologic and geobarometric data. Clark et al (2005) concluded that the southern Sierra experienced two stages of uplift since 32 Ma that brought the elevation to 4 km that is observed today from the roughly 1.5 km prevailing through the early Cenozoic.…”
Section: Palaeoaltitude Of the Great Basin Areamentioning
confidence: 99%
See 1 more Smart Citation